2015
DOI: 10.1186/s12884-015-0597-x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between self-reported perinatal outcomes and administrative data in New South Wales, Australia

Abstract: BackgroundMany epidemiological studies that focus on pregnancy rely on maternal self-report of perinatal outcomes. The aim of this study was to evaluate the agreement between self-reported perinatal outcomes (gestational hypertension with or without proteinuria, gestational diabetes, premature birth and low birth weight) in a longitudinal study and linked to administrative data (medical records).MethodsSelf-reported survey data from the Australian Longitudinal Study on Women’s Health was linked with the New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 30 publications
4
42
2
Order By: Relevance
“…Diagnosis was confirmed with a 75 g OGTT (fasting) with a venous plasma glucose level at 0 h of ≥5.1% (5.6 mmol/l) and/or at 2 h of ≥6.65% (8.0 mmol/l) [24]. A reliability study among a subgroup of women from New South Wales (n=1,914) demonstrated high agreement of 91% between self-reported GDM diagnosis in our study and administrative data records [25].…”
Section: Assessment Of Gdmsupporting
confidence: 67%
“…Diagnosis was confirmed with a 75 g OGTT (fasting) with a venous plasma glucose level at 0 h of ≥5.1% (5.6 mmol/l) and/or at 2 h of ≥6.65% (8.0 mmol/l) [24]. A reliability study among a subgroup of women from New South Wales (n=1,914) demonstrated high agreement of 91% between self-reported GDM diagnosis in our study and administrative data records [25].…”
Section: Assessment Of Gdmsupporting
confidence: 67%
“…8,9 In 2002, a study in Wollongong found around 50% of women with GDM were missed in the private hospital setting. 10 While there was a strong correlation between Ministry records and other reported data, including hospital records, 11,12 and maternal self-reports, 13 no reviews have been carried out on what is not recorded, and this is critical. Ways to overcome this problem have been suggested, 10 and considered, 14 but not implemented.…”
Section: Discussionmentioning
confidence: 99%
“…If high risk (obese) or low risk (under/normal weight) women differentially reported their GDM status, associations could have been biased to either direction. However, selfreported weight has shown to be a reliable estimate [26] and a high level of agreement between self-reported physician diagnosed GDM and the medical record has been also found in a subpopulation of this cohort [20]. Associations were adjusted for a variety of risk factors of GDM, but unmeasured factors such as family history of GDM or diabetes, ethnicity and gestational weight gain may have introduced residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis was confirmed with a 75 g oral glucose tolerance test (fasting) with a venous plasma glucose level at 0 hour of ≥ 5.6 mmol/l and/or at 2 hours of ≥ 8.0 mmol/l [19]. Recently, in a subpopulation of the ALSWH 1973-78 cohort (n = 1,914), a validation study between selfreported perinatal outcomes and medical records showed a high level of agreement (>92%), between self-reported physician diagnosed GDM and the medical record [20].…”
Section: 3ascertainment Of Gdmmentioning
confidence: 99%